Time Effectiveness and Cost Efficiency with Crashing Method, Overlapping, and Combined in Los Development Project Ngadiluwih Market - Eni Nur Safitri; Inge Anggitasari; Susilowati Susilowati; Olvi Pamadya Utaya K (Journal of Innovative and Creativity, 2026)
Background: The Ngadiluwih Market Los construction project in Kediri is experiencing potential delays with a normal duration of 210 days and a RAB of Rp12.55 billion, requiring optimization of time and costs through crashing, overlapping, and a combination of these to meet the final target of 2025. Objective: To analyze the effectiveness of the crashing method (overtime and additional labor/equipment), overlapping, and their combination using Microsoft Project. Research Type and Method: Descriptive quantitative through literature studies, field observations, and critical path analysis. Population and Sample: All project activities (210 days); purposive sampling of critical paths such as excavation, foundation, and steel structure based on the RAB and schedule of consultant CV. DAWS Architects. Analysis Instruments and Techniques: Microsoft Project and Excel for cost slope, crashing (additional human resources/tools), overlapping (changing FS relationship to SS/FF with lag), and cost/duration comparison. Results: The combined crashing method added labor/equipment and overlapping was the most optimal with a duration of 137 days (saving 73 days) and cost efficiency of IDR 218 million (ratio 0.983). Conclusion: The combined crashing-overlapping approach is superior for accelerating traditional market construction projects, with recommendations for adoption in similar PUPR projects for maximum